Issues in Capturing and Utilizing Non-Functional Requirements along the Road to Servitization. (May 2022) - Toller, C. N. K.; Johansson, C.; Bertoni, M.
Abstract: The design process aims to maximize the value in the end solution. For traditional manufacturing firms pursuing a servitization strategy, non-functional requirements become more important compared to before. Therefore, this paper investigates issues in capturing and utilizing non-functional requirements for value creation in a servitizing firm. A single case study was conducted, which resulted in six issues across the design process. It was evident from the research that the firm requires new support to enable a better inclusion of non-functional requirements in the design process.